PENGHINDARAN PAJAK DALAM PERSPEKTIF KEUANGAN PERUSAHAAN: TINJAUAN LITERATUR ATAS PERAN PROFITABILITAS DAN LEVERAGE - Widiyati, Dian; Nurmadina, Tia (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
Tax is one of the largest revenue sectors in the APBN posture which is used to improve people's welfare. However, many companies as taxpayers try to avoid taxes. This study aims to determine the effect of profitability and leverage variables on tax avoidance practices. The research method used is systematic literature review by searching for journals relevant to the topic. This study is limited to companies listed on the IDX in the property & real estate, manufacturing, and IDX80 index sectors. The results of the study found that there was inconsistency in the effect of profitability and leverage on tax avoidance. Several researchers stated that there was a significant positive effect between profitability and leverage on tax avoidance. Other researchers showed the opposite results. Profitability and leverage actually have a negative effect on tax avoidance. Through this study, it is hoped that it can provide benefits for interested parties to pay more attention to these actions. The government can be wiser in making policies to improve taxpayer compliance.